Q Determination of Transmission GPR Waves in Absorbing Media - Ibrahim, Eddy; Parnadi, Wahyudi W (Review of Information Engineering and Applications, 2015)
The absorption of electromagnetic waves is the most important parameter for the processing and interpretation of Ground-Penetrating Radar (GPR) data. Both the phase velocity and the absorption coefficient are frequency-dependent. From the linear basis of the frequency dependence of of geology media, a constant Q-hypothesis is valid, whereby the Q factor is inversely proportional to and describes material-specific absorption. For the near-reality description of electromagnetic waves propagation in rocks, modeling with constant Q and velocity dispersion after Futterman is carried out. On the basis of such model, the effect of these parameters on wavelets is investigated. As a result of absorption, the wave amplitudes become smaller with increasing distance at the same Q and become smaller with decreasing Q at the same distance and the waveforms are stretched . The longer the distance at the same Q as well as the smaller Q at the same distance, the smaller is the bandwidth of the transmission wavelets. At the same time, its peak frequency moves toward smaller frequencies. In addition, three methods for the determination of the absorption through Q factor are reviewed, namely the spectral ratio method, amplitude decay method and a method over absorption coefficient determination. The applicability of the methods is then demonstrated by using real data acquired from transmission measurement at test site in Reiche Zeche Shaft in Germany.